3(x+5)=x-10

Simple and best practice solution for 3(x+5)=x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+5)=x-10 equation:


Simplifying
3(x + 5) = x + -10

Reorder the terms:
3(5 + x) = x + -10
(5 * 3 + x * 3) = x + -10
(15 + 3x) = x + -10

Reorder the terms:
15 + 3x = -10 + x

Solving
15 + 3x = -10 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
15 + 3x + -1x = -10 + x + -1x

Combine like terms: 3x + -1x = 2x
15 + 2x = -10 + x + -1x

Combine like terms: x + -1x = 0
15 + 2x = -10 + 0
15 + 2x = -10

Add '-15' to each side of the equation.
15 + -15 + 2x = -10 + -15

Combine like terms: 15 + -15 = 0
0 + 2x = -10 + -15
2x = -10 + -15

Combine like terms: -10 + -15 = -25
2x = -25

Divide each side by '2'.
x = -12.5

Simplifying
x = -12.5

See similar equations:

| 3535x-5725x+58y=4734z | | a/4-3/4=1/3 | | y^2-12y+27= | | X^5-4x^4+7x^3-10x^2+10x-4=0 | | A=(7x)(3x) | | -7x-3=13 | | 9.5=0.4(5x)+2.5 | | 9x+1=5x+15 | | 7*y-3=2*y-3 | | x^2-10x+25=x^2-8x+16+1 | | (x-5)=(x-4) | | 10(2x-10)=0 | | 3*200=2+x | | ln(x+8)-ln(x-2)=ln(x+2) | | h=-16t^2+250 | | a-1=14 | | 2x-5=8x+7-4x | | 4(2z+1)-6=70 | | x^2-10x+25-1=0 | | 24x+3=51 | | 12x+6y=8 | | 9(z+1)-2(z-4)=3(z-2)+3(z-4) | | 25+5n=9(7n+4) | | 3x^2-22x+16=0 | | +2.25-13.5=9 | | 5x+2(y+8)=18 | | 10t-5+4t=10-t | | 10x-(5x-8)=33 | | 18.5p+7=-15+6.5p | | 4x+12=4x-12 | | 0=2x^3-9x^2+x+12 | | sqrtx+9=4 |

Equations solver categories